2017
DOI: 10.4236/tel.2017.73037
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Information and the Implied Volatility: Evidence from India VIX

Abstract: The present study attempts to examine the scheduled macroeconomic announcement effects on the India VIX using OLS regression model and the EGARCH model. The empirical results show that the information content of macroeconomic news on report day and day after does not have significant influences on India VIX, except MCIR. Besides, the findings reveal no significant response of India VIX during one day before the scheduled news announcements. This is due to the fact that India VIX market is more uncertain before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…A study by Srinivasan (2017) attempted to understand the effect of scheduled macroeconomic announcement on Indian implied volatility by using EGARCH and OLS models. The study results found that the scheduled macroeconomic announcements and information content does not have any significant impact on Indian Implied volatility Heejoon Han, Ali M. Kutan, and Doojin Ryu (2015) examined the ability of macroeconomic and financial variables in forecasting the Korea's implied volatility index (VKOSPI) using augmented heterogenous autoregressive models (HAR) with exogenous variables.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Srinivasan (2017) attempted to understand the effect of scheduled macroeconomic announcement on Indian implied volatility by using EGARCH and OLS models. The study results found that the scheduled macroeconomic announcements and information content does not have any significant impact on Indian Implied volatility Heejoon Han, Ali M. Kutan, and Doojin Ryu (2015) examined the ability of macroeconomic and financial variables in forecasting the Korea's implied volatility index (VKOSPI) using augmented heterogenous autoregressive models (HAR) with exogenous variables.…”
Section: Introductionmentioning
confidence: 99%